2015
DOI: 10.1371/journal.pone.0122828
|View full text |Cite
|
Sign up to set email alerts
|

Can Reproductive Health Voucher Programs Improve Quality of Postnatal Care? A Quasi-Experimental Evaluation of Kenya’s Safe Motherhood Voucher Scheme

Abstract: This study tests the group-level causal relationship between the expansion of Kenya’s Safe Motherhood voucher program and changes in quality of postnatal care (PNC) provided at voucher-contracted facilities. We compare facilities accredited since program inception in 2006 (phase I) and facilities accredited since 2010-2011 (phase II) relative to comparable non-voucher facilities. PNC quality is assessed using observed clinical content processes, as well as client-reported outcome measures. Two-tailed unpaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
(36 reference statements)
2
26
0
Order By: Relevance
“…Since vouchers schemes subsidizes on LTFP methods at voucher facility, it is expected that there is an increased supply of the methods within the facility and thus healthcare providers providing such services to OBA clients. The results are congruent to a study done in Kenya which showed that there may have been an increased utilization in family planning and thus spillover effect as a result of stocking contraceptive methods within the facilities [17]. …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Since vouchers schemes subsidizes on LTFP methods at voucher facility, it is expected that there is an increased supply of the methods within the facility and thus healthcare providers providing such services to OBA clients. The results are congruent to a study done in Kenya which showed that there may have been an increased utilization in family planning and thus spillover effect as a result of stocking contraceptive methods within the facilities [17]. …”
Section: Discussionsupporting
confidence: 86%
“…Overall, the total utilization of LTFP method among OBA clients is significantly higher compared to Non OBA clients. The findings are supported by a study done in Kenya which showed that increased utilization amongst OBA clients may have been due to increased family planning advice by the health care providers in the OBA facilities [17]. Since vouchers schemes subsidizes on LTFP methods at voucher facility, it is expected that there is an increased supply of the methods within the facility and thus healthcare providers providing such services to OBA clients.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…quality of PNC at facilities 21,22 may have prompted women to leave facilities sooner than the recommended 48-hour stay. Our results are consistent with the poor utilization of PNC reported globally.…”
Section: Discussionmentioning
confidence: 99%
“…Some more recent evidence points to improvements in both the quantity and quality of care provided by voucher service providers (Watt et al 2015;Kanya 2013).…”
Section: Introductionmentioning
confidence: 99%